We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
57
1
avatar

Simplify (x+1)(2x+3)(3x+4) = (6x^{2}+5)(x-3)$ to the form $0 = Ax^{2}+Bx+C, where A, B, and C are positive integers with a greatest common divisor of 1. What is A+B+C?

 May 13, 2019
 #1
avatar+116 
+3

Just to reformat your question for my aesthetic quick;

 

Simplify \((x+1)(2x+3)(3x+4) = (6x^{2}+5)(x-3)\) to the form \(0 = Ax^{2}+Bx+C\) where A, B, and C are positive integers with a greatest common divisor of 1. What is \(A+B+C\)?

 

\((x+1)(2x+3)(3x+4) = (6x^{2}+5)(x-3)\)

\((2x^2+3x+2x+3)(3x+4) = 6x^3-18x^2+5x-15\)

\((2x^2+5x+3)(3x+4)=6x^3-18x^2+5x-15\)

\(6x^3+8x^2+15x^2+20x+9x+12=6x^3-18x^2+5x-15\)

\(6x^3+23x^2+29x+12=6x^3-18x^2+5x-15\)

\(41x^2+24x+27=0\)

\(Ax^2 + Bx + C = 0\)

\(A = 41, B = 24, C = 27\)

\(A + B + C = 41+24+27=92\)

.
 May 14, 2019

12 Online Users